Yona of the dawn. 23 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2020)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-Won. But everything changes on her 16th birthday when tragedy strikes her family!... Yona gets caught in the middle of the nation of Xing's civil unrest after she discovers that Princess Kouren wants war against the kingdom of Kohka! As Princess Kouren stokes the fire of the pro-war faction, Yona must find a way to save the Dragon Warriors and her home country!"--Provided by publisher.